Subwavelength focusing of terahertz waves using self-similar chain of designer plasmon resonators - Dong, Zihao (Nanyang Technological University, 2020)
The rapid development of terahertz technology in recent years has provided a basis for the application of terahertz technology. Because of the unique superiority and huge application prospects of terahertz in many important fields, it is gradually revealed. According to previous data, it is shown that metamaterials with specific structures can induce the multipolar spoof localized surface plasmons. Last semester we have formed a self-similar chain based on ultra-thin circular spiral structures as plasmonic resonators. Use the superfocus effect to achieve terahertz through CST studio simulation software. The energy of the band is strengthened. This article is mainly based on circular plasmonic resonators. We have also designed square and asymmetric plasmonic resonators for comparison.